Resolving Optical and Catalytic Activities in Thermoresponsive Nanoparticles by Permanent Ligation with Temperature‐Sensitive Polymers. (11th July 2019) - Chen, Yihuang; Wang, Zewei; Harn, Yeu Wei; Pan, Shuang; Li, Zili; Lin, Shaoliang; Peng, Juan; Zhang, Guangzhao; Lin, Zhiqun
Abstract: Thermoresponsive nanoparticles (NPs) represent an important hybrid material comprising functional NPs with temperature‐sensitive polymer ligands. Strikingly, significant discrepancies in optical and catalytic properties of thermoresponsive noble‐metal NPs have been reported, and have yet to be unraveled. Reported herein is the crafting of Au NPs, intimately and permanently ligated by thermoresponsive poly( N ‐isopropylacrylamide) (PNIPAM), in situ using a starlike block copolymer nanoreactor as model system to resolve the paradox noted above. As temperature rises, plasmonic absorption of PNIPAM‐capped Au NPs red‐shifts with increased intensity in the absence of free linear PNIPAM, whereas a greater red‐shift with decreased intensity occurs in the presence of deliberately introduced linear PNIPAM. Remarkably, the absence or addition of free linear PNIPAM also accounts for non‐monotonic or switchable on/off catalytic performance, respectively, of PNIPAM‐capped Au NPs. Abstract : Von einem anderen Stern : Dauerhaft gebundene thermoresponsive Nanopartikel mit abstimmbaren Abmessungen und Zusammensetzungen wurden durch die Nutzung des sternförmigen Diblock‐Copolymers PNIPAM als Nanoreaktor hergestellt. Ermittelte Daten der temperaturabhängigen optischen und katalytischen Eigenschaften zeigten zwei offenbar widersprüchliche Beobachtungen auf, die sich jedoch abgleichen ließen.